JUDICIAL REVIEW MAHKAMAH KONSTITUSI TENTANG STATUS ANAK DI LUAR NIKAH - Asep O Akbar (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2012)
This study focuses on adjudication of the judges of MK in which in the tradition of law research, it is called law propositions. It means that based on ideal scientific activities of law science, this study enables to cover several activities: inventories, interpreting, systemizing, and evaluating rules of law, both written and unwritten. According to Gustav Radbruch, of all four activities, interpreting and systemizing are more important. Idealization of such a scientific activity will just get the precision of its verification when it has been completed try an empirical research through deep interviews with the judges of MK. All this time, the writer’s has not conducted distillation or construed the law hidden behind the texts of law. This paper is the writer's initial observation or his preliminary research. Based on religious and law norm of the material of adjudication of judicial review of MK, this study is still normative. According to the writer, the characteristics of the adjudication of the judges of MK is a crucial point or a hard case because it deals with the sensitive areas covered several dimensions such as religion, human right, nationalistic politics. The writer argues that such a kind of crucial adjudication is not proper if the judges only rely on the procedures of formal law, but it needs an innovation or rule of breaking as a form of law innovation (rechtsvinding), indeed rechtsvinding plus. This is a farm of law construction, in which in the tradition of inference of Islamic law it is similar to logical reasoning “al-'illah al mustanbathah”: to reach beneficence in the context of state life.Keywords: Mashlahah, rechtsvinding, diyani, qadlai